Negative impact of skeletal muscle impairment in older patients with heart failure with reduced versus preserved ejection fraction. (25th November 2020) - Konishi, M; Kagiyama, N; Saito, H; Saito, K; Ogasahara, Y; Maekawa, E; Kitai, T; Momomura, S; Tamura, K; Kimura, K; Kamiya, K; Matsue, Y
Abstract: Background/Introduction: Reduced functional capacity is an important phenotype of heart failure (HF), even though it may be considered multifactorial, especially in HF with preserved ejection fraction (HFpEF). Impairment in skeletal muscle may be one of extra-cardiac factors for reduced functional capacity and subsequent poor outcome. Purpose: We sought to investigate the impact of the impairment in skeletal muscle, defined by the cut-offs proposed by the international consensus, on functional capacity and clinical outcome, in HF patients with preserved and reduced EF (HFrEF). Methods: This is a multicenter prospective study including 1317 consecutive older (≥65 years) hospitalized patients with HF [HFpEF (ejection fraction ≥45%, n=675, 82±7 years, 46.4% male) and HFrEF (ejection fraction <45%, n=642, 78±8 years, 68.4% male)]. Results: HFrEF patients were more likely to have low skeletal muscle mass measured by bioelectrical impedance analysis (30.9% vs 22.1%, p=0.003) whereas less likely to have low muscle strength (handgrip strength; 62.9% vs 73.8%, p<0.001) than HFpEF, resulting in similar prevalence of sarcopenia between the two groups (21.6% vs 18.1%, p=0.19). In HFrEF, presence of sarcopenia was an independent predictor of reduced functional capacity assessed by a 6-minute walk distance (standardized beta=−0.093, p=0.039 in multivariate linear regression analysis) and 1-year mortality (adjusted hazard ratio (aHR) and 95% CI; 2.14 (1.22–3.70), p=0.009 in multivariate Cox-regression analysis). In patients with HFpEF, sarcopenia could predict mortality (aHR and 95% CI; 2.23 (1.23–3.91), p=0.009), though its association with reduced functional capacity was not significant after multivariate adjustment (standardized beta=−0.059, p=0.20). Kaplan-Meier survival curves in HFpEF and HFrEF are shown (Figure). Conclusion(s): In older patients with HF, sarcopenia was similarly contributed to mortality in HFpEF and HFrEF whereas its influence on functional capacity was pronounced in HFrEF. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Japan Heart Foundation Research Grant